DETERMINAN EKSPOR KOMODITAS RUMPUT LAUT DI PROVINSI SULAWESI TENGGARA - Musdalifah Musdalifah; Mohammad Natsir; Syafiuddin Syafiuddin (Universitas Galuh, 2022)
Seaweed is one of the important export fishery commodities in Indonesia. The study aims to analyze factors affecting seaweed commodity exports in Southeast Sulawesi Province. This research uses quantitative approach methods. The data used is secondary data of quarterly time series in the time span between 2017-2021. The data source was obtained from the Central Statistics Agency (BPS) and the Fisheries and Marine Service. The data is analyzed using multiple linear regression analysis. The results showed that the dollar exchange rate, seaweed production, and inflation simultaneously had a significant effect of 96.76 percent on the value of seaweed exports in Southeast Sulawesi. Variable dollar exchange rate and production have a significant effect, on the export value of seaweed. Production negatively affects the value of exports, if seaweed production rises by one million tons then the export value decreases by Rp 7,029.54. The value of the dollar exchange rate has a positive effect on the value of seaweed exports, if the value of the dollar rate rises by a thousand rupiah then the export value of seaweed increases by Rp 216,593.50. Inflation has no significant effect on the export value of seaweed. The value of the dollar rate is the most important variable in influencing the value of sea exports.